Centralidade e influência internacional: A experiência da fundaç\~ao da cidade do Salvador sob o ciclo econômico do pau-brasil; Centralization and international influence: The experience of the founding of the city of Salvador in pau-brasil of the economic cycle - Paulo Patrício Costa; Tatiana Spinola (European Regional Science Association (ERSA), 2015)
– This article proposes an analysis of central places, both the size of the urban center as the size of the regional centrality, as a product of international interests (exogenous), using the historical case study methodology, adopting as its object a theme widely considered to be exhausted that is the Salvador city's founding and of course, the first steps of the Brazilian nation, with an analysis will from their first economic cycle: pau-brasil cycle. In the construction of ideas and historical recovery favors the tertiary sector, seeking concrete historical evidence of its slow socioeconomic acceptance until the advent of capitalism. Makes a rereading the concept of formation of cities and your metabolism and some of its intrinsic elements. Concluded that there was no intention by the Portuguese founder in creating a centrality in the size of the urban center, which for lack of an internal market took more than fifty years based on trade in basic subsistence products, however Salvador was born as the main regional centrality of the southern hemisphere of the sixteenth century remained in this condition until the seventeenth century.
Keywords: 330